A Case of Atypical Bartonellosis in a 4-Year-Old Immunocompetent Child - Chiara Sodini; Elena Mariotti Zani; Francesco Pecora; Cristiano Conte; Viviana Dora Patianna; Giovanni Prezioso; Nicola Principi; Susanna Esposito (Microorganisms, 2021)
In most cases, infection due to Bartonella henselae causes a mild disease presenting with a regional lymphadenopathy frequently associated with a low-grade fever, headache, poor appetite and exhaustion that spontaneously resolves itself in a few weeks. As the infection is generally transmitted by cats through scratching or biting, the disease is named cat scratch disease (CSD). However, in 5–20% of cases, mainly in immunocompromised patients, systemic involvement can occur and CSD may result in major illness. This report describes a case of systemic CSD diagnosed in an immunocompetent 4-year-old child that can be used as an example of the problems that pediatricians must solve to reach a diagnosis of atypical CSD. Despite the child’s lack of history suggesting any contact with cats and the absence of regional lymphadenopathy, the presence of a high fever, deterioration of their general condition, increased inflammatory biomarkers, hepatosplenic lesions (i.e., multiple abscesses), pericardial effusion with mild mitral valve regurgitation and a mild dilatation of the proximal and medial portion of the right coronary artery, seroconversion for B. henselae (IgG 1:256) supported the diagnosis of atypical CSD. Administration of oral azithromycin was initiated (10 mg/kg/die for 3 days) with a progressive normalization of clinical, laboratory and US hepatosplenic and cardiac findings. This case shows that the diagnosis of atypical CSD is challenging. The nonspecific, composite and variable clinical features of this disease require a careful evaluation in order to achieve a precise diagnosis and to avoid both a delayed diagnosis and therapy with a risk of negative evolution.